2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Work Opportunity Tax Credits (WOTC) Federal - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS)
The Work Opportunity Tax Credits (WOTC) program provides tax credits for employers who hire certain targeted categories of individuals. This is EDIS document FE421, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.